ChemInform Abstract: Glycoclusters on Oligonucleotide and PNA Scaffolds: Synthesis and Applications. Issue 33 (25th July 2013) - Spinelli, Nicolas; Defrancq, Eric; Morvan, Francois
Abstract Review: 59 refs.